Human Papillomavirus DNA extraction and genotype analysis by multiplex real time polymerase chain reaction from formalin fixed paraffin wax-embedded cervical carcinoma specimens - Price, Brendon (Department of Pathology, 2020)
Introduction: Cervical squamous cell carcinoma is most commonly caused by persistent infection by high risk human papillomavirus (hrHPV) genotypes. The exact type of hrHPV varies geographically and is the basis for HPV–based vaccination for cervical squamous cell carcinoma prevention. Little is known regarding local hrHPV genotypes within the Western Cape population of South Africa. Aims and objectives: This was a pilot study aiming to extract of high quality genomic DNA from archival FFPE cervical squamous cell carcinoma cases and identify hrHPV genotypes by multiplex real time PCR (RT-PCR). Materials and methods: A retrospective search identified a total of 57 cases of cervical squamous cell carcinoma for the period 2004-2014. This was reduced to a final number of 23 that exhibited sufficient tumour burden for DNA extraction. The most common age group was 40-49 years. HIV status was as follows: two HIV-positive, 14 HIV-negative and 7 HIV unknown. DNA was extracted from archival FFPE cervical squamous cell carcinoma samples using QIAGEN QIAamp® DNA FFPE Tissue kit. Housekeeping genes were detected by endpoint PCR using standard primers for glyceraldehyde 3-phosphate dehydrogenase (GAPDH) sequences to determine the quality and integrity of extracted DNA for downstream PCR amplification experiments. HrHPV DNA amplification was optimised using a touchdown PCR technique with L1 consensus gene GP5+/GP6+ primers. HrHPV genotypes were detected using a four colour multiplex hrHPV genotyping kit. Samples showing positive results in overlapping probe filter detection spectra were subjected to DNA Sanger sequencing for final confirmation of specific hrHPV genotype. Results: Standard xylene DNA extraction methods using QIAamp® system yielded adequate amounts of DNA with average final concentration of 463.2 ng/l and A260/A280 ratio of 1.86. Housekeeping genes were successfully detected in all samples, confirming that no significant DNA degradation of target sequences occurred within the archival time range of 2004-2014. HPV L1 detection via GP5+/GP6+ primers with endpoint PCR was not achieved via standard cycling conditions and required the use of a touchdown technique with gradually decreasing annealing temperatures. This method successfully identified HPV L1 sequences in 22 out of 23 cases. Multiplex RT-PCR with four colour hydrolysis probes identified hrHPV genotypes in 22 of 23 cases with relative frequencies of HPV genotypes: 16>>18=39=45>33. Most cases showed infection with a single hrHPV genotype (HPV 16 and one case with HPV 33) with four cases demonstrating two genotypes (two with HPV 16&18, one with 16&33 and one with 39&45) and one case with three genotypes (HPV 16, 39, 45). Interestingly, none of the HIV-positive cases showed multiple hrHPV genotype infection. Four hrHPV cases with overlapping spectra for HPV 18/31 and 45/59 were subjected to Sanger sequencing for confirmation of genotype. Three of four cases showed 100% match for genotypes 18 and 45 with the final case demonstrating only co-infective HPV 16.Conclusion: Commercial DNA extraction kits yield adequate amounts of intact, amplifiable DNA in archival FFPE cervical carcinoma specimens. Touchdown PCR is necessary for HPV detection in extracted FFPE DNA cases using GP5+/GP6+ L1 primers. RT-PCR using multicolour hydrolysis probes is a rapid, sensitive technique for hrHPV genotype screening of cervical squamous cell carcinoma specimens. A three colour detection system rather than four colour kit is recommended for future studies in order to avoid extra cost in DNA sequencing cases with overlapping spectra. This pilot study demonstrates hrHPV genotype prevalence similar to that in other populations and suggests that vaccination with currently available formulations would provide a sufficiently wide coverage of HPV genotypes. Future studies will include application of the FFPE DNA extraction, endpoint PCR and RT-PCR techniques to the remainder of the cases in the original cohort.